Learning Sign Language through Bisindo-based Choreographic Process - Riana Diah Sitharesmi (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Creating dance requires movements vocabularies as well as the proficiency of choreographic technique.  The significant forms intent to present some visual codes or signs for the spectators to capture the hidden messages. Contemporary dance vocabularies can be obtained by elaborating visual codes that exist in everyday life, including codes used by the Deaf for communication.  Contemporary choreography using Bisindo is used as a medium for dance students to learn sign language, as part of their contribution to inclusivity at Gorontalo. This research implicates a qualitative phenomenological perspective on studio work that involve an artistic-based research as method in analysing the process of dance creation.  Referring to Hadley, Humphrey, Smith, and Lavender in organizing contemporary dance repertoires in the context of the Deaf – Hearing intersection, this research integrates the basic elements of Bisindo as prime movement vocabularies. The research completed the artistic process, but has not reach the choreographic construction to integrate the Deaf with her Hearing mates. The results of the research are a dance movement vocabulary based on Bisindo, an inclusive arts learning model, and a contemporary dance repertoire. The choreography process and a dance piece entitled ‘Tanda Tanda Berkata’ provide an artistic medium for dance students to learn basic sign language, thus it also bridge the communication gap with deaf friends.